ANALISIS FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN GO PUBLIC YANG MASUK DALAM INDEKS KOMPAS 100 DENGAN STRUKTUR MODAL SEBAGAI VARIABEL INTERVENING - Astohar Astohar; Dhian Andanarini Minar Savitri (Among Makarti, 2019)
AbstractThis research perfecting the research conducted by Hermuningsih (2013) and build structural factors that affect the value of customers who are affected by the growth opportunities and profitability either directly or through capital structure. The model is constructed by adding liquidity variable,  measured by current ratio. The variables chosen to flesh out the previous model due to the current ratio of debate still going on against the capital structure or the value of the company. The increase of the v liquidity variable expected able to fine-tune the structural model was built. Selected research objects are Kompas index 100 at Indonesia stock exchange in the period up to 2013 until 2017. Large samples are required for the research is as much as 100 companies that are consecutive – undertook to enter into Kompas Index 100 for five consecutive years – co-designer with sampling techniques using purposive non random sampling. Analysis tool used is the regression equation, i.e. first is the influence of liquidity, profitability and growth opportunities to the structure of capital. The second regression model is the influence of liquidity, growth opportunities, profitability and capital structure of the company.  The research shows the Current ratio (CR) proved to have a negative and significant effect against the capital structure. Return on equity (ROE) proved to have a positive and significant effect against the value of the company. Asset growth opportunities are not proven to have a negative and significant effect against the capital structure. Current ratio (CR) proven asset growth opportunities have a positive and significant effect against the value of the company. Capital structure (debt to equity ratio) is not proven to mediate the effect of liquidity, profitability and growth opportunities of the company. Keywords : likuiditas, growth, profitabilitas, struktur modal dan nilai perusahaan